Compared to the results of international referees and first-class tests Cooper football referees - Ali Nassif, Mohsen (Journal of Physical Education, 2012)
The study aimed to compare the results between the rulers and the international first-class tests Cooper's fitness and the differences for the times and distances traveled during the tests and the number (8) international referees and (8) referees assistants.Conclusions not to give enough rest between the tests of the referees (fitness), which impact negatively on the results of the tests especially the third and fourth tests in addition to the weak performance of the speed of the rulers of the first class